2008
DOI: 10.1002/crat.200800058
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of selenium of different morphologies at room temperature

Abstract: A facile and convenient chemical precipitation route has been developed for the controlled growth of selenium nanowires and hierarchical microspheres at room temperature, with Na 2 SeO 3 and hydrazine hydrate as starting materials in the presence of 1,2,3-trimethylimidazolium tetrafluoroborate (tmimBF 4 ). The surface morphology of microspheres can be tuned by adjusting the reaction media. The products were characterized by X-ray powder diffraction (XRD) and scanning electron microscope (SEM). Possible formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The formation of elemental selenium of different morphologies was carried out in 1,2,3-trimethylimidazolium tetrafluoroborate, but no details of its solubility are noted. 10 In this work, ionic liquids are shown to be safe alternatives to conventional solvents for sulfur, and they can be designed to give the greatest known solubility for sulfur in any solvent (at atmospheric pressure). 11 A number of readily available ionic liquids were tested for sulfur solubility at elevated temperatures.…”
mentioning
confidence: 99%
“…The formation of elemental selenium of different morphologies was carried out in 1,2,3-trimethylimidazolium tetrafluoroborate, but no details of its solubility are noted. 10 In this work, ionic liquids are shown to be safe alternatives to conventional solvents for sulfur, and they can be designed to give the greatest known solubility for sulfur in any solvent (at atmospheric pressure). 11 A number of readily available ionic liquids were tested for sulfur solubility at elevated temperatures.…”
mentioning
confidence: 99%
“…Other studies reported that trigonal selenium nanowires were synthesised by chemical methods in a physical way. For example, trigonal selenium (t-Se) nanowires and microspheres were synthesised at room temperature by the chemical precipitation method using hydrazine hydrate as precipitator in the presence of 1,2,3-trimethylimidazolium-tetrafl uoroborate (tmimBF4) with sodium selenite (Ma et al, 2008). Similarly, trigonal selenium nanowires were successfully synthesised via low-temperature hydrothermal synthesis route.…”
Section: Selenite Reduction With Chemical Agentsmentioning
confidence: 99%
“…Most recently, the advantages of ILs in inorganic synthesis have been gradually realized, and a few inorganic nanomaterials with novel morphologies and special properties have been prepared in ILs, such as TiO 2 nanocrystals, Fe 2 O 3 nanostructures, Se microspheres, and ZnSe hollow nanospheres [12][13][14][15]. However, the exploration of ILs for the synthesis of inorganic nanomaterials is still in its infancy, and the application of ILs in inorganic synthesis should be intensively investigated.…”
Section: Introductionmentioning
confidence: 99%